Biological and proteomic characterization of a composite mesh for abdominal wall hernia treatment: Reference Study. Issue 7 (8th July 2016) - Vozzi, Federico; Guerrazzi, Ilenia; Campolo, Jonica; Cozzi, Lorena; Comelli, Laura; Cecchettini, Antonella; Rocchiccioli, Silvia; Domenici, Claudio
ABSTRACT: Aims: The industrial development of a product requires performing a deep analysis to highlight its characteristics useful for future design. The clinical use of a product stimulates knowledge improvement about it in a constant effort of progress. This work shows the biological characterization of CMC composite mesh. CMC polypropylene prosthesis was seeded with Human fibroblast BJ. Samples (cells and medium) were collected at different time points in order to perform different analysis: inflammatory markers quantification; collagens immunohistochemistry; matrix metalloproteinases zimography; extracellular matrix proteomic profile. Findings: CMC presented a good cell viability rate and cell growth during the 21 days. The inflammatory profile showed an initial secretion of anti‐inflammatory IL‐10 and a final increase of pro‐inflammatory IL‐6. Immunocytochemistry highlighted a similar Collagen type I/type III ratio. The proteomic analysis evidenced the ECM protein content profile composed, mainly, by collagens, fibronectin, laminin. MMPs resulted both expressed when in contact to mesh. Conclusions: CMC shows a good cell biocompatibility and growth. The increase of pro‐inflammatory markers could stimulate proliferation, influencing the integration process in human body. Proteomics highlights the ECM modulation by CMC. An integrated investigation of these biological analyses with mechanical data should improve the design process of a new product. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 2045–2052, 2017.